Chapters from Economic Theories on Hysteresis - Posgay, István; Regős, Gábor; Horváth, Diána; Molnár, Dániel (Public Finance Quarterly, 2019)
Since the economic and financial crisis of 2008, proposals on economic policy devised on the basis of hysteresis have become the focus of economic sciences. This study presents some theories on the 2008 crisis and subsequent hysteresis, as well as related economic policy proposals. The crisis and hysteresis acted as theoretical catalysts and, by expanding the boundaries of previous main theories, sometimes produced significant results, and continue to do so to this very day. Hysteresis is also significant from the point of view of the Hungarian economy, as the crisis has hit the country particularly hard. However, as a result of the post-2010 economic policy shift, the government has been able to rebalance and put the economy back on a growth path. This can also be called a positive hysteresis, as the economy is growing steadily and faster than expected based on this trend.